Enhancing 4th-grade Students’ Interest and Science Learning Outcomes through Differentiated Learning: A Quasi-Experimental Study at SD Muhammadiyah Kleco Kotagede, Yogyakarta - Iim; Maryani, Ika; Suparman; Kuswana, Sugesty Linda (Journal of Pedagogy and Education Science, 2025)
The issue in science learning is the mismatch between the applied learning model and student characteristics, along with teachers' limited pedagogical abilities. This impacts students' interest and learning outcomes in science. This study aims to examine the effect of differentiated learning on students' interests and science learning outcomes. The research uses a quasi-experimental design with a two-group pretest-posttest control group approach. Data were collected through observations, a learning interest questionnaire, and a learning outcomes test. Simple random sampling was used, involving two classes: IV Tablig (28 students) and IV Amanah (29 students). Validity was tested using point biserial, and reliability was measured with KR-20. Data analysis included descriptive statistics and hypothesis testing using the Paired Sample t-test and Independent Sample t-test.  Results showed that after the intervention, students' interest in science learning was in the moderate category (39.29%), and learning outcomes were also moderate (50%). The Paired Sample t-test indicated a significant improvement in interest and learning outcomes, while the Independent Sample t-test confirmed a significant difference between the experimental and control groups. Thus, differentiated learning has a significant effect on students' interest and science learning outcomes.